GOOD CORPORATE GOVERNANCE (GCG) IN MUNICIPALLY OWNED COMPANY (MOC) IN SOUTH KALIMANTAN - Fifi Swandari; Abdul Hadi (UPT Penerbitan Universitas Jember)
Implementation of GCG in Municipally Owned Companies (MOC) are usually still low, that was indicated by the low GCG score. The purposes of this research are to describe and analyze the implementation of GCG in MOC in South Kalimantan and to analyze the differencess of implementation between tow companies. This research is qualitative research and can be categorized as case study. Two municipally owned companies are selected. Keyperson from two companies are interviewed, with deep interviewed. Key points of GCG implementation are asked to them, include the threat to make good implementataion of GCG. The result, only one of MOC has had GCG formally, the other hasn’t. It means one of MOC has the mechanisms, processes and relations by which corporations are controlled and directed at the formal level, and the implementation was improve from time to time. There are many differences in implementation of GCG from two companies. Importance recomendation is issuing Perda to push MOC make implementation of GCG.